From the Lisbon Strategy to Europe 2020: the Statistical Landscape of the Education and Training Objectives Through the Lens of the Capability Approach - Josiane Vero (Social Work and Society)
The aim of this chapter is to bring together and comment official statistics and indicators that make up educational targets that are increasingly favoured in the European Union Policy context from the Lisbon Strategy to the Europe 2020 strategy. Focusing on the call for making young people more employable, the chapter relies on Amartya Sen's Capability Approach and in particular on his key idea of "˜informational basis of judgement' to reveal the postulates behind the benchmarks that assess progress toward the Education and Training Strategy. Taking up this plea, the chapter starts out by giving a brief description of the Lisbon Strategy as well as the Europe 2020 Strategy. In this perspective, it reports what progress in education and training- or lack of it - has taken place. The subsequent section introduces the concepts of"capability" and"Informational basis of judgement" derived from Amartya Sen's Capability Approach (CA) in order to shed light on the normative postulates underlying the benchmarks promoted by the European Commission . One main focus lies in addressing limitations of these indicators with the aim of providing a practical instrument with which to assess and compare education and training performance. The chapter concludes by offering some thoughts for an alternative set of indicators that employs insights from the capability approach drawn from the work of Amartya Sen.